Pharmaceutical Care in Depression: A Survey of Stigma, Confidence, Attitudes, and Barriers - Soliman M (Dove Medical Press, 2020)
Moetaza Soliman Department of Pharmacy Practice, Faculty of Pharmacy, Mansoura University, Mansoura, ElDakahlia, EgyptCorrespondence: Moetaza SolimanDepartment of Pharmacy Practice, Faculty of Pharmacy, Mansoura University, ElGomhoria Street, Mansoura, ElDakahlia, EgyptEmail moetaza13@yahoo.comPurpose: Patients with depression are in high need of optimal pharmaceutical care as they have poor quality of life and functioning. However, little is known about the delivery of pharmaceutical care to patients with depression in Egypt. This study aimed to detect pharmacists’ stigma of patients with depression, assess attitudes toward providing depression care, evaluate pharmacists’ confidence with depression medication consultation, and identify barriers in providing pharmaceutical care to patients with depression.Methods: A cross-sectional survey was posted on the social media websites of Egyptian pharmacists’ groups and associations. The survey collected pharmacists’ demographic information, then measured their confidence in medication consultation through the Pharmacists’ Confidence scale about Medication Consultation for Depressive Patients (PCMCD), with items to assess stigma of patients with depression and attitudes toward providing care to patients with depression compared with other physical conditions. The pharmacists were also asked about the barriers to providing pharmaceutical care to patients with depression.Results: Totally, 86 pharmacists completed the survey: 56 (65.1%) were aged 30 years or older, and 64 (74.6%) had more than five years of experience. The stigma of patients with depression was generally low. The mean (SD) PCMCD score was 51.4 (6.6), reflecting that most pharmacists were confident about medication consultation for patients with depression. Attitudes toward providing pharmaceutical care to patients with depression were generally positive but significantly lower than those reported for patients with other conditions. Lack of education on mental health was the most commonly reported barrier (81.2%) to providing pharmaceutical care to patients with depression.Conclusion: Participants were confident about medication consultation with a positive attitude toward providing pharmaceutical care. Frequent mental health educational courses, tools, and other methods of consistent engagement that enhance practice, behaviors, and outcomes should be considered for Egyptian pharmacists to improve pharmaceutical care provided to patients with depression.Keywords: PCMCD score, cross-sectional, Egyptian pharmacists, medication consultation